2019
DOI: 10.1021/acsaelm.9b00394
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Stability and Ambipolar Charge Transport in Diketopyrrolopyrrole-Based Organic Materials

Abstract: An important strategy for realizing flexible complementary circuits with organic semiconductors is to achieve balanced ambipolar charge transport properties with reduced anisotropy. Here, we present a series of star-shaped diketopyrrolopyrrole (DPP) based organic materials synthesized for improved intermolecular charge transport while retaining the ambipolar charge transport properties of their linear counterparts. Steady-state UVvisible spectroscopic studies confirm that the oligomers are highly aggregated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…An optimal balance between conductivity and Seebeck coefficient maximizes the power factor, which, in turn, controls the thermoelectric conversion for useful power extraction. 7 The concentration of charge carriers (ρ) strongly governs σ and S and hence PF. 8 Optimizing PF is quite challenging 9 because each of its two factors has a complicated and contrary dependence on the carrier concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An optimal balance between conductivity and Seebeck coefficient maximizes the power factor, which, in turn, controls the thermoelectric conversion for useful power extraction. 7 The concentration of charge carriers (ρ) strongly governs σ and S and hence PF. 8 Optimizing PF is quite challenging 9 because each of its two factors has a complicated and contrary dependence on the carrier concentration.…”
Section: Introductionmentioning
confidence: 99%
“…There is a trade-off between Seebeck coefficient and electrical conductivity (σ) because doping leads to higher carrier concentration, thereby boosting conductivity while simultaneously reducing the difference between Fermi and transport levels and thus the Seebeck coefficient. An optimal balance between conductivity and Seebeck coefficient maximizes the power factor, which, in turn, controls the thermoelectric conversion for useful power extraction . The concentration of charge carriers (ρ) strongly governs σ and S and hence PF .…”
Section: Introductionmentioning
confidence: 99%
“…Among the OSC molecules, much interest has been placed on thiophenes. ,,, One group of molecules with thiophene repeats, which has attracted much attention due to their high carrier mobilities and stable performance in OFETs and OPVs, is diketopyrrolopyrrole (DPP) derivatives. , A less investigated DPP derivative is the n -dialkyl side-chain-substituted thiophene DPP end-capped with a phenyl group (Ph-TDPP-Ph), which has a broadband absorption spectrum up to ∼650 nm and can be both solution-processed and vacuum-deposited, making it interesting for devices that require absorption over most of the visible spectrum. , One of the few studies on Ph-TDPP-Ph by Pickett et al investigated the correlation between the microstructure of Ph-DPP-Ph and charge transport in Ph-TDPP-Ph OFETs. The authors found that Ph-TDPP-Ph adopts two different crystalline phases in thin-film form, with one phase having significantly higher charge carrier mobility (by 2–3 orders of magnitude); however, it was not clear how to process the thin film in order to obtain the phase with the higher carrier mobility.…”
Section: Introductionmentioning
confidence: 99%
“… 67 , 68 In search of ambipolar organic semiconductors, our group has developed a novel series of DPP-based alternating copolymers. 74 78 Surprisingly, simple molecular engineering has led to a remarkable improvement in electron mobility (∼3 cm 2 V −1 s −1 ) in OFETs and acts more like conventional inorganic semiconductors with a band-like transport. 79 , 80 Till date, Ajayaghosh and co-workers demonstrated 2D nanosheets of the self-assembly layer under organic and aqueous conditions by substituting hydrophilic and hydrophobic groups with DPP, 81 showing a anisotropic charge-carrier mobility of 0.33 cm 2 V –1 s –1 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the substituted DPP with the appropriate donor group shows high thermal stability, fluorescent quantum yield, and exhibit enhanced charge-carrier mobility. In recent years, DPP derivatives have shown a potential application in the field of molecular-based optoelectronic devices such as organic electrochemical transistors (OECTs), organic thermoelectric materials (OTEs), OFETs, and OPVs. , In search of ambipolar organic semiconductors, our group has developed a novel series of DPP-based alternating copolymers. Surprisingly, simple molecular engineering has led to a remarkable improvement in electron mobility (∼3 cm 2 V −1 s −1 ) in OFETs and acts more like conventional inorganic semiconductors with a band-like transport. , Till date, Ajayaghosh and co-workers demonstrated 2D nanosheets of the self-assembly layer under organic and aqueous conditions by substituting hydrophilic and hydrophobic groups with DPP, showing a anisotropic charge-carrier mobility of 0.33 cm 2 V –1 s –1 .…”
Section: Introductionmentioning
confidence: 99%